Intracerebroventricular Administration of an Endothelin ETB-Receptor Agonist Increases Expression of Matrix Metalloproteinase-2 and -9 in Rat Brain - Yutaka Koyama; Kazuhiro Tanaka (Elsevier, 2010)
Abstract.: Matrix metalloproteinases (MMPs), a family of zinc-endopeptidases, have a critical role in the pathophysiological responses in damaged brains. MMPs are up-regulated in brain pathologies. To clarify the extracellular signals involved in brain MMP production, the effects of endothelins (ETs), a family of vasoconstricting peptides, were examined. Intracerebroventricular administration of 500 pmol/day Ala1,3,11,15-ET-1, an ETB-receptor agonist, increased the mRNAs of MMP2 and MMP9 in rat hippocampus and cerebrum. Ala1,3,11,15-ET-1 did not affect mRNA levels of MMP 1, 12, and 14. Administration of Ala1,3,11,15-ET-1 for 7 days also increased the protein content and proteolytic activities of MMP2 and MMP9 in the cerebrum. Immunohistochemical observations showed that astrocytes in the hippocampus and the cerebrum of ET-infused rats had MMP2 and MMP9 reactivities. In rat cultured astrocytes, both Ala1,3,11,15-ET-1 (100 nM) and ET-1 (100 nM) increased MMP2 and MMP9 mRNAs. ET-1 stimulated the protein releases and the proteolytic activities of MMP2 and MMP9 from cultured astrocytes. BQ788, an ETB antagonist, inhibited the effects of ET-1 on astrocytic MMP2 and MMP9. The ET-induced expression of MMP9, but not MMP2, was inhibited by pyrrolidine dithiocarbamate, proteasome inhibitor I, and MG132. These results suggest that ET stimulates astrocytic MMP2 and MMP9 production through ETB receptors. Keywords:: endothelin-1, matrix metalloproteinase (MMP), astrocyte, brain injury, gene expression